Šalies miestų planavimui taikomos gyvenamųjų vietovių klasifikacijos ir jų funkcinės sandaros apibrėžimas - Daunora, Zigmas Jonas (Journal of Architecture and Urbanism, 2006)
Classification of Lithuanian towns and definition of their functional structure used for urban planning purposesComprehensive planning of towns and townships takes a wider scale in the country. Therefore, there appears an urgent need to revise or review some conceptions of planning methodology that should be accepted after various alternatives consideration. According to our opinion (a) classification of centres of a settlement system (towns and townships) requires self-determination and equal understanding which, from one side, should reflect more precisely the existing diversity of development between the centres and their functions and, from the other side, the rank granted to these centres should meet the EU criteria; (b) the functional structure of towns and townships, reflected by diversity in the purpose of their territory use and its indefinite character during the process of residential area modernization which takes place under market conditions, forces to give upa detailed setting of plot purpose and look for a more universal model of land- use purpose specification which could be applicable not only for planning of rural agricultural territories but for urban planning of residential areas as well.Proposals presented in the paper (Tables 1 and 2) respect the systematic conception of settlement network, accepted in Lithuania and in the other EU countries and based on the hierarchy of elements and development dependency allowing application of sustainability and balance principles for the system element development. They are prepared taking into account new urban planning conceptions and reflecting the following factors:• changing business and production conditions as well as growing qualitative safety, service and ecological requirements for a residential environment;• increasing importance of economic factors and resulting need for a more rational land use and broader urban internal integration when developing public transportation and urban system for a common space use;• respect to stable urban structural elements of residential areas (urban framework) as well as to local cultural identity and historically formed compositional peculiarities;• advantages of the functional and social diversity and polycentric character of urban structures.Article in Lithuanian.Santrauka. Pristatomi atliktos analizės rezultatai, susiję su Lietuvos gyvenamųjų vietovių bendrojo planavimo metodikos tobulinimo uždaviniais, iškilusiais susidūrus su jų plėtros neapibrėžtumu rinkos sąlygomis vykstančiame miestų modernizacijos procese. Platesniam aptarimui siūloma (a) gyvenviečių sistemos centrų (miestų ir miestelių) klasifikacija, paremta tikslesniu jų išsivystymo lygio bei atliekamų funkcijų apibrėžimu ir centrams teikiamo rango ES taikomiems kriterijams atitikimu; (b) universalesnis žemės naudojimo paskirties specifikacijos modelis, kuris būtų tinkamas ne tik kaimiškųjų teritorijų žemėtvarkos planams rengti, bet ir miestų bendrojo planavimo uždaviniams spręsti.Reišminiai žodžiai: miestas, teritorija, planavimas, metodika, klasifikacija, specifikacija.First Published Online: 22 May 2013